THE STATE OF HORMONAL LEVELS IN PATIENTS WITH CHRONIC PROSTATITIS ON THE BACKGROUND OF SEXUALLY TRANSMITTED INFECTIONS - R. A. Sadretdinov; L. P. Voronina; O. S. Polunina; A. A. Polunin; I. A. Erina (Кубанский научный медицинский вестник, 2016)
It was studied the state of hormonal levels in fertile and infertile patients with chronic prostatitis on a background of sexually transmitted infections (STIs). The study included 280 patients with chronic prostatitis, distributed into four groups: 70 fertile patients without STIs, 70 fertile patients with STIs, 70 infertile patients without STIs and 70 infertile patients with STIs. The control group consisted of 50 healthy men of reproductive age. It is revealed that in the group of infertile patients with chronic prostatitis with STIs, there are mixed changes in levels of sex hormones. In the group of fertile patients with chronic prostatitis a link between the level of sex hormones with the presence of STIs have been identified.